Structure and antimycobacterial activity of the novel organometallic [Pd(C-bzan)(SCN)(dppp)] compound - Ferreira, Janaina G. [UNESP]; Stevanato, Alessandra [UNESP]; Santana, Anderson M.; Mauro, Antonio Eduardo [UNESP]; Netto, Adelino Vieira de Godoy [UNESP]; Frem, Regina Célia Galvão [UNESP]; Pavan, Fernando R. [UNESP]; Leite, Clarice Q. F. [UNESP]; Santos, Regina H. A. (Elsevier B.V., 2012)
The organometallic compound [Pd(C-bzan)(SCN)(dppp)] {bzan = N-benzylideneaniline, dppp = 1,3-bis(diphenylphosphino)propane} was synthesized and characterized by elemental analyses, infrared and H-1 and P-31(H-1) NMR spectroscopies. The crystal and molecular structures of the title complex were determined by single-crystal X-ray diffraction techniques. In vitro antimycobacterial evaluation demonstrated that the compound [Pd(C-bzan)(SCN)(dppp)] displayed a MIC of 5.15 mu M, which is superior than those values found for some commonly used anti-TB drugs and other Pd(II) complexes. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Organometallic Pd(II) compound; 1,3-bis(Diphenylphosphino)propane; Mycobacterium tuberculosis